Formulation and Optimization of Matrix Tablets Based on Spirulina and Vitamin C - ASSANHOU, Assogba Gabin; YEMOA, Loconon Y. Achille (My University, 2023)
Spirulina is a type of algae widely consumed around the world as a dietary supplement due to its great nutritional potential. However, it does not contain vitamin C, a vital vitamin for the proper functioning of the human body, particularly given its immunostimulant potential. The objective of this work was to formulate sustained release spirulina–vitamin C matrix tablets that would enhance particularly a prolonged release and better absorption of vitamin C. A galenic formula based only on vitamin C was made, and then the proportion of vitamin C was reduced in favor of spirulina powder. The manufactured tablets were then subjected to various pharmacopeial quality control tests. The results of these tests showed a good distribution of the powder mixtures in the formulated tablets (i.e., mass uniformity test) and satisfactory outcomes were found for the content uniformity, disintegration and dissolution tests (with 45 % of vitamin C dissolved after 4 hours). Only the results for the friability test were unsatisfactory, indicating the need to improve the physical properties of the powders before compression. These findings open a new area for developing supplementary dietary.
Keywords: Spirulina; Vitamin C; Matrix tablet; Quality control.